2018
DOI: 10.1186/s12960-018-0273-0
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of the treatment of uncomplicated severe acute malnutrition by community health workers compared to treatment provided at an outpatient facility in rural Mali

Abstract: BackgroundThe Malian Nutrition Division of the Ministry of Health and Action Against Hunger tested the feasibility of integrating treatment of severe acute malnutrition (SAM) into the existing Integrated Community Case Management package delivered by community health workers (CHWs). This study assessed costs and cost-effectiveness of CHW-delivered care compared to outpatient facility-based care.MethodsActivity-based costing methods were used, and a societal perspective employed to include all relevant costs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 18 publications
6
33
1
1
Order By: Relevance
“…This study shows that children receiving SAM treatment from CHWs generally exhibited a less severe stage at admission, with lower rates of edema and better anthropometric condition compared to children treated at HFs. A previous analysis on the cost-effectiveness of this new approach for SAM management with CHWs as treatment providers showed that families can save half the time and one-third of the money that it would cost to treat their children at the HFs [22]. This cost-saving could prevent families from delaying the initiation of required nutritional treatment, allowing children to be admitted in a relatively less severe condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study shows that children receiving SAM treatment from CHWs generally exhibited a less severe stage at admission, with lower rates of edema and better anthropometric condition compared to children treated at HFs. A previous analysis on the cost-effectiveness of this new approach for SAM management with CHWs as treatment providers showed that families can save half the time and one-third of the money that it would cost to treat their children at the HFs [22]. This cost-saving could prevent families from delaying the initiation of required nutritional treatment, allowing children to be admitted in a relatively less severe condition.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the operational experiences of this approach has recently been published [9] and shows that programs implementing this new community approach can achieve better outcomes in terms of recovery and defaulter rates than standard CMAM programs performed at HFs far away from the affected villages. This review also found that the iCCM+ model could potentially double the coverage of SAM treatment services, achieving over 80% treatment coverage in a cost-effective manner, reducing the time and money that the families would expend to treat their children at the health centers, which are usually located far away from their households [10,11].…”
Section: Introductionmentioning
confidence: 92%
“…This is in support of findings from a study conducted in Mali assessing the cost-effectiveness of treatment of uncomplicated SAM using CHWs and outpatient facilities. In this study, treatment using CHWs was cost-effective 64 .…”
Section: Discussionmentioning
confidence: 88%
“…The review identified four studies assessing costs incurred by community volunteers during the implementation of CMAM 24,62, 64,65 . Two studies conducted in Mali and Pakistan compared the cost effectiveness of treatment of uncomplicated SAM by community health workers (CHWs) to outpatient facility based programs 64,65 . The study in Mali reported that delivery of treatment by CHWs ($259 per child recovered) was more cost-effective compared to the outpatient facility care ($501 per child).…”
Section: Community Volunteers Perspectivementioning
confidence: 99%
“…Additional cost‐effectiveness evidence is provided by the Mali study, where services provided in the facility (control group) were compared with services provided in a facility and by CHWs at household level (intervention group; Rogers et al, ). Authors applied a similar societal perspective with an activity‐based costing analysis.…”
Section: Resultsmentioning
confidence: 99%